2005
DOI: 10.1007/s00404-005-0102-2
|View full text |Cite
|
Sign up to set email alerts
|

The value of pronuclear scoring for the success of IVF and ICSI-cycles

Abstract: Benefit from pronuclear scoring seems to be small. Apparently, experienced biologists are able to select "good-quality" pronuclear oocytes in the same way they would do after scoring. However, the results might be biased by differences between the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…PN scoring was postulated to provide predictive value of embryo development, even of the chromosomal constitution and implantation potential of the embryo (Gianaroli et al, 2007;Montag and van der Ven, 2001;Salumets et al, 2003;Scott and Smith, 1998;Scott et al, 2000;Tesarik and Greco, 1999;Wittemer et al, 2000). Therefore, PN scoring is widely used to predict embryo fate, but is of course, the subject of a controversial debate (James et al, 2006;Ludwig et al, 2006;Payne et al, 2005). Many investigators have found a relationship between PN scoring and improved embryo development/blastocyst formation (Balaban et al, 2001;Nagy et al, 2003;Rienzi et al, 2002;Zollner et al, 2002) and/or increased pregnancy and implantation potential (Montag and van der Ven, 2001;Wittemer et al, 2000;reviewed by Zollner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…PN scoring was postulated to provide predictive value of embryo development, even of the chromosomal constitution and implantation potential of the embryo (Gianaroli et al, 2007;Montag and van der Ven, 2001;Salumets et al, 2003;Scott and Smith, 1998;Scott et al, 2000;Tesarik and Greco, 1999;Wittemer et al, 2000). Therefore, PN scoring is widely used to predict embryo fate, but is of course, the subject of a controversial debate (James et al, 2006;Ludwig et al, 2006;Payne et al, 2005). Many investigators have found a relationship between PN scoring and improved embryo development/blastocyst formation (Balaban et al, 2001;Nagy et al, 2003;Rienzi et al, 2002;Zollner et al, 2002) and/or increased pregnancy and implantation potential (Montag and van der Ven, 2001;Wittemer et al, 2000;reviewed by Zollner et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The insemination of the oocytes was performed using standard procedures for IVF or ICSI as previously described elsewhere (21)(22)(23) and was performed 39 to 42 hours after the hCG injection. Fertilization was confirmed 16 to 20 hours after oocyte retrieval by the presence of two distinct pronuclei and polar bodies under the inverted microscope.…”
Section: Fertilization Pronuclear Scoring and Embryo Culturementioning
confidence: 99%
“…Pattern 0 [6] and Z1 or Z2 [10] have been associated with an increase in implantation and pregnancy rates [7,8,[11][12][13][14][15]. Recently however, a number of investigators have not been able to demonstrate an association between PN scoring and improved ART outcomes [16][17][18].…”
Section: Introductionmentioning
confidence: 99%